Optimising Arabic Language Localisation In E-Commerce Marketing: A Qualitative Study Of User Experience, Trust, And Cultural Adaptation - Mohammad Rifqi Junaidi; Nur Arifuddin; A. Samsul Ma’arif; Bakri Muhammad Bakhiet (Lahjatuna: Jurnal Pendidikan Bahasa Arab, 2026)
This study examines the optimisation of Arabic as a strategic marketing asset in e-commerce platforms targeting Arabic-speaking consumers, particularly in the Middle East. Using a qualitative approach, the study draws on secondary data from academic literature, industry reports, policy documents, and digital observations of selected platforms such as Amazon.ae and Noon.com. The data were analysed thematically to identify patterns related to Arabic interface design, localised marketing content, cultural adaptation, consumer trust, and platform competitiveness. The findings show that Arabic optimisation improves e-commerce competitiveness by enhancing platform accessibility, strengthening consumer trust, increasing user engagement through culturally relevant marketing, and supporting customer retention through Arabic-based services. The study also highlights challenges such as dialect variation, translation quality, right-to-left interface integration, and localisation costs. The novelty of this article lies in positioning Arabic not merely as a translation medium, but as a strategic marketing resource that integrates linguistic, cultural, technological, and commercial dimensions. These findings provide practical implications for global e-commerce companies seeking to expand into Arabic-speaking markets.